Correlation of the inclination of the incisors to the stability of the alignment of the anterior sector, based on PAR index criteria - Juan Carlos Rodriguez-Ladino; Sonia Patricia Plaza-Ruíz; Judith Patricia Barrera-Chaparro; Ivonne Liliana Barrero-Avellaneda; Lizeth Meriño-Brochero; Ángela Paola Ramírez-Herrera (Universidad de Antioquia, 2022)
Introduction: the objective of this study was to evaluate the relationship between incisor inclination at the end of orthodontic treatment with the anterior teeth alignment stability using PAR index. Methods: analytical cross-sectional study, the angle formed between the plane (Silla-Nasion) (U1-NS) and the inclination of the upper incisor and the angle between axial inclination of the lower incisor and mandibular plane (Go-Gn), were measured in 47 initial and final lateral radiographs of patients who finished orthodontic treatment. The anterior sector PAR index was applied to pretreatment (T0), posttreatment (T1) and follow-up (T2) casts. Statistical analysis was performed using frequency and percentage distributions, T test, Anova I, Anova II and Manova; significance p = 0,05. Results: no association was found between upper and lower incisor inclination, alignment stability and PAR weighted score between T2-T1 (p> 0,05). The PAR decreased 75,29% from T0 to T1 and 58,79% from T0 to T2, with a recurrence of 16,5%. There was no association between retainer type and PAR weighted score. From T0 to T2 there was an association between the interaction of the incisor inclination of upper (p = 0,03) and lower (p = 0,04), with the weighted total score of the PAR index. Conclusion: there was no association between the modification of the incisor inclination with the stability of the anterior sector. At the end of orthodontic treatment there was a high level of correction in the anterior-superior and inferior sector, however, there was a recurrence of 16,5%.